ACG Clinical Guideline: Alcohol-Associated Liver Disease - Jophlin, Loretta L.; Singal, Ashwani K.; Bataller, Ramon; Wong, Robert J.; Sauer, Bryan G.; Terrault, Norah A.; Shah, Vijay H. (The American journal of gastroenterology, 2024)
ABSTRACTAlcohol-associated liver disease (ALD) is the most common cause of advanced hepatic disease and frequent indication for liver transplantation worldwide. With harmful alcohol use as the primary risk factor, increasing alcohol use over the past decade has resulted in rapid growth of the ALD-related healthcare burden. The spectrum of ALD ranges from early asymptomatic liver injury to advanced disease with decompensation and portal hypertension. Compared with those with other etiologies of liver disease, patients with ALD progress faster and more often present at an advanced stage. A unique phenotype of advanced disease is alcohol-associated hepatitis (AH) presenting with rapid onset or worsening of jaundice, and acute on chronic liver failure in severe forms conveying a 1-month mortality risk of 20%-50%. The model for end stage disease score is the most accurate score to stratify AH severity (>20 defined as severe disease). Corticosteroids are currently the only available therapeutic with proven efficacy for patients with severe AH, providing survival benefit at 1 month in 50%-60% of patients. Abstinence of alcohol use, a crucial determinant of long-term outcomes, is challenging to achieve in ALD patients with concurrent alcohol use disorder (AUD). As patients with ALD are rarely treated for AUD, strategies are needed to overcome barriers to AUD treatment in patients with ALD and to promote a multidisciplinary integrated care model with hepatology, addiction medicine providers, and social workers to comprehensively manage the dual pathologies of liver disease and of AUD. Liver transplantation, a definitive treatment option in patients with advanced cirrhosis, should be considered in selected patients with AH, who are unresponsive to medical therapy and have a low risk of relapse to posttransplant alcohol use. Level of evidence and strength of recommendations were evaluated using the Grading of Recommendations, Assessment, Development, and Evaluations system. This guideline was developed under the American College of Gastroenterology Practice Parameters Committee.